Implementasi Kebijakan Ekonomi Hijau dalam Mendukung Pembangunan Nasional Berkelanjutan Secara Inklusif - Azizah Arfah; Handar Subhandi Bakhtiar; Atik Winanti (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
This study discusses the comparison of green economic policies implemented between Indonesia and Malaysia in supporting inclusive sustainable national development, which is examined normatively through a comparative study approach. Indonesia, through Law No. 30 of 2007 on Energy, Law No. 21 of 2014 on Geothermal Energy, and other regulations, has established a national green program encompassing environmental quality improvement, disaster resilience and climate change mitigation, low-carbon development, and renewable energy development as pillars of national development. Meanwhile, Malaysia's National Energy Policy 2022-2040 and other regulations stipulate that a green economy can be achieved through economic development, the utilization of sustainable energy resources, and environmental quality. Research findings indicate that Indonesia has not maximized the implementation of a green economy due to the ease of business permits granted to investors and limited regulations within specific scopes, while Malaysia has established more complex regulations regarding green investments, ensuring that permits are not issued arbitrarily.